Dynamic route switching protocol in mobile ad hoc networks. (25th May 2006) - Ssu, Kuo-Feng; Chou, Chih-Hsun; Chiu, Chi-Sheng
Due to limited bandwidth, "how to decrease routing overhead" is an important issue in mobile ad hoc networks. Several multipath routing protocols have been proposed to reduce the frequency of route discovery. However, in rapidly changed network topologies, some backup paths may be broken before a host uses them. Additionally, to obtain multiple loop-free paths, some protocols only select backup paths that are equal or shorter than the first found path. Longer routing paths are discarded even if they can stay available longer than the primary path. This paper presents a dynamic route switching protocol (DRSP) to locate more useful and longlived routing paths. The protocol not only considers node mobility but energy consumption also. Based on the prediction, expired backup paths are erased automatically so that the possibility of unsuccessful delivery can be reduced. The mobility prediction can also adjust appropriate transmission power. The DRSP protocol was implemented on ns-2 and evaluation results show that the DRSP outperformed AODV, DSR, and AOMDV.